Degradation of polyethylene plastic bags and bottles using microorganisms isolated from soils of Morogoro, Tanzania - Nakei, Monica D.; Misinzo, Gerald; Tindwa, Hamisi; Semu, Ernest (Frontiers in Microbiology, 2022)
Plastics are of great significance in today’s world due to their extensive use such as packaging food and carrying other goods, which have improved the quality of human life. However, plastics have low biodegradability and are persistent in the environment, becoming a major source of pollution. With regard to the current methods used in the management of plastic wastes, the degradation of plastics using beneficial soil microorganisms has recently gained attention due to their ability to degrade different types of plastics including polyethylene (PE) polymers. The study herein was conducted to isolate and identify microorganisms from agricultural soils capable of degrading plastics. Soil samples were inoculated into nutrient, potato dextrose, and starch-casein agar for the isolation of bacteria, fungi, and actinomycetes, respectively. During isolation, fungi and bacterial plates were incubated for 5 days and for 14 days, respectively. The population of bacteria ranged from 1 × 105 to 1.215 × 105 and that of fungi from 1.604 × 104 to 8.6 × 104 whereby actinomycetes ranged from 1.045 × 105 to 2.995 × 105 CFU/g of soil. However, the tested microorganisms showed significant (p ≤ 0.05) differences in the ability to degrade PE bags and bottles as depicted by the diameters of clear zones around the colonies. The diameters of clear zones ranged from 19.3 to 47.5 mm and 25.9 to 32.2 mm after 17 days for bacteria and actinomycetes, respectively, and those of fungi ranged from 30.0 to 66.3 mm after 13 days. Among the bacteria, actinomycetes, and fungi, unsequenced bacterial and actinomycete isolates B1 and A3 as well as Aspergillus sp. (F7) were the most efficient degraders of PE plastic bags. This retrospective study sheds light on our understanding and the need for the bioprospecting of agricultural soils, water bodies, and landfills containing plastic wastes that could lead to the identification of more efficient microbial species with the ability to degrade plastics.